The mythical landscapes of the Greek goddess Artemis in the literary texts of the Hellenistic poets Callimachus, Apollonius of Rhodes and Theocritus - Salas-Moya, Jenny (2023)
This article identifies, based on epithets and myths, the landscapes of the Greek goddess Artemis in two specific literary genres of the Hellenistic Age, the Epic and the Lyric, in order to analyze the deity from territorial elements. The analysis depicted a goddess Artemis who could be described as ecumenical. This universality, acquired as a result of the coexistence of multiple and varied cultures during the time, materialized with a total cosmopolitan domain. The quintessential landscape of the goddess was that of the cities with all the elements that constituted them.